A plane vertical submerged barrier in surface water waves - U. Basu; B. N. Mandal (International Journal of Mathematics and Mathematical Sciences)
By a simple application of Green's integral theorem, amplitude of the radiated waves at infinity due to a line source in the presence of a fixed vertical plane barrier completely submerged in deep water is obtained.